Methanation of Carbon Monoxide and Carbon Dioxide on Raney Nickel, and Computer Simulation of Chain Growth in the Fischer-Tropsch Synthesis - Lee, Boon Chung (My University, 1982)
The methanation of carbon monoxide and carbon dioxide was studied over Raney nickel. The catalyst was characterized by chemisorption techniques. A differential plug-fIow reactor was used to obtain kinetic data. The reaction rates were investigated as a function of temperature, reactants and products concentrations. The power rate law was found inadequate in representing the kinetic data of carbon dioxide methanation. The orders of reaction for hydrogen and carbon monoxide were obtained. Carbonaceous species were found on the catalyst surface after methanation reaction, which could react with hydrogen give methane. Multilayers of carbon species were deposited on the catalyst surface during CO methanation; less than a monolayer was found when carbon dioxide was used as feed. The effects of reaction conditions on the amount of residual carbon was also investigated.
The data in general agrees with a mechanism involving the hydrogenation of carbonaceous species as the rate determining step. The differences between CO and CO₂ methanations were also discussed.
The carbon chain growth process in the Fischer-Tropsch synthesis was simulated using available data in the literature. The simulation was done by representing the hydrocarbon chains by numbers stored in vectors. Various chain growth schemes were tested. The results suggested that the carbon chain growth process could involve the stepwise additions of both one-carbon and two-carbon units.
Keywords: Chemical Engineering; Chemical Engineering